Legalitas Penerbitan Sertifikat Hak Atas Tanah Di Atas Kawasan Lindung Sempadan Danau Toba - Naibaho, Jeremy Aidianto (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
Tourism is one of the national strategic projects that is expected to improve the community's economy, one of the tourism area is the Lake Toba. This causes the community try to cultivate and posses the land around Lake Toba, including at the lake border area. The Lake Toba border area which is a protected but it is densely populated with community activities, including plantation activities, aquaculture, residential areas and hotel buildings. The large number of activities in the Lake Toba border area is caused by the absence of definite rules regarding the Lake Toba border. The purpose of this study was to assess the validity of issuing certificates of land rights belonging to the people on the shores of Lake Toba. Furthermore, this research is a normative legal research (library research) with a statutory approach.